Clinicopathologic Features and Outcome of Young Adults With Stage IV Colorectal Cancer. (December 2015) - Hawk, Natalyn N.; Long, Tua-Elisabeth; Imam, Muhammad H.; Mathew, Blessy M.; Kim, Sungjin; Chen, Zhengjia; Goodman, Michael; Sullivan, Patrick; Brutcher, Edith; Kauh, John; Maithel, Shishir K.; Adsay, Volkan N.; et al.
Abstract : Purpose: Colorectal cancer has a distinct clinicopathologic presentation in younger patients. The aim of this paper was to evaluate the outcome of younger (age below 50 y) and older patients with stage IV (advanced) colorectal cancer in the modern era of combination chemotherapy. Methods: Cases of metastatic colorectal cancer reported in Surveillance, Epidemiology, and End Results registry (1973 to 2008) were reviewed. Demographics, tumor characteristics, and overall and cancer-specific survivals in patients below 50 and above 50 years of age were compared by Cox proportional hazard analyses. Joinpoint regression analysis was used to evaluate secular trends in 2-year survival. Results: Younger patients had a greater proportion of negative clinicopathologic features (male sex, African American ethnicity, and signet ring or mucinous histology). In multivariate analysis, older age, male sex, African American ethnicity, right-sided tumors, and signet ring histology were associated with higher mortality risk. Younger patients had improved survival (hazard ratio 0.72; 95% confidence interval: 0.70-0.75) compared with older patients, whereas all patients experienced increased 2-year survival by joinpoint analysis beginning in 1999-2000. Conclusions: The results confirm decreased mortality from advanced colorectal cancer in the era of modern combination chemotherapy in younger and older patients. Younger age, non–right-sided tumors, and absence of signet ring histology significantly associate with better survival.